The Tragedy of the Uncommons: On the Politics of Apocalypse. (May 2016) - Wiener, Jonathan B.
Abstract: The 'tragedy of the commons' is a classic type of problem, involving multiple actors who face individual incentives to deplete shared resources and thereby impose harms on others. Such tragedies can be overcome if societies learn through experience to mobilize collective action. This article formulates a distinct type of problem: 'the tragedy of the uncommons', involving the misperception and mismanagement of rare catastrophic risks. Although the problem of rare and global catastrophic risk has been much discussed, its sources and solutions need to be better understood. Descriptively, this article identifies psychological heuristics and political forces that underlie neglect of rare catastrophic 'uncommons' risks, notably the un availability heuristic, mass numbing, and underdeterrence. Normatively, the article argues that, for rare catastrophic risks, it is the inability to learn from experience, rather than uncertainty, that offers the best case for anticipatory precaution. The article suggests a twist on conventional debates: in contrast to salient experienced risks spurring greater public concern than expert concern, rare uncommons risks exhibit greater expert concern than public concern. Further, optimal precaution against uncommons risks requires careful analysis to avoid misplaced priorities and potentially catastrophic risk–risk trade‐offs. The article offers new perspectives on expert vs public perceptions of risk; impact assessment and policy analysis; and precaution, policy learning and foresight. Abstract : Expert analysis is crucial not only because of public neglect of uncommons risks, but also because the case for increasing attention to rare extreme uncommons risks does not necessarily mean that these risks outweigh or deserve greater priority than other serious current and chronic risks, nor does it directly point to optimal policy responses.